The Quality of Strengthening Impregnation of 3D-Printed Parts for Agricultural Machinery - R. Ya. Kazberov; S. P. Tuzhilin (Сельскохозяйственные машины и технологии, 2022)
It is noted that the level of mechanical properties of polymer products manufactured with the help of traditional technologies exceeds that of products made by 3D printing. The relevance of studying various methods of strengthening 3D printed products is shown, for example, the method of vacuum impregnation in epoxy compounds. (Research purpose) To determine the dependence between the quality of impregnation of 3D printed parts of agricultural machinery and the viscosity of the impregnating epoxy compound selected. (Materials and methods) The viscosity of the impregnating epoxy compound was changed by adding such diluents as acetone and DEG-1. The viscosity of the compound was measure by a rotational viscometer. The magneto drive pinion of the MTZ tractor starting engine and the auger pin support of the John Deere cutter bar were chosen as the objects for impregnation. The components were produced by a 3D-printer using FDM technology. After impregnation, the products were cut in certain sections to assess the existence of unfilled areas. The amount of resin hardened on the product surface was estimated. (Results and discussion) It has been found that acetone reduces viscosity 2 times more efficiently than DEG-1. Since acetone cost is lower, it was used for the subsequent experiments. For the impregnation of agricultural machinery parts, three levels of viscosity were chosen: the high level, corresponding to the 16 pascal-seconds initial viscosity of epoxy compound; the average level of 8.8 pascal-seconds, corresponding to the injection of 0.5 percent of acetone (by weight); the low level of 6.5 pascal-seconds, corresponding to the injection of 1.5 percent acetone (by weight). It was found that products impregnated with high and low viscosity compounds contained many pores in cross sections and a large amount of compound on the surface. (Conclusions) Based on the results of impregnation, the best composition proves to be that with the epoxy resin viscosity of 8.8 pascal-seconds corresponding to 0.5 percent of acetone (by weight). It is proved that the higher compound viscosity does not allow it to eff ectively penetrate into the product, at a lower viscosity, on the contrary, the compound leaks out of the product after impregnation.